Data-Driven Analysis of Cyber Threats and Public Policy Responses in Indonesia - Eka Septi Nur Jannah; Dini Eka Prasasti; Nada Alfaiza Fisabilazkia (Goodwood Publishing, 2026)
Purpose: This study aims to examine cybersecurity vulnerabilities in Indonesia’s digital public service transformation using a data-driven public policy perspective and to generate evidence-based policy recommendations. Research Methodology: This study applies a qualitative data science approach by combining systematic policy review with social media analytics. Public discourse on cybersecurity incidents was collected from Platform X through data scraping and analyzed using Orange software for sentiment analysis, keyword mapping, and temporal visualization to assess public perception and governance-related risks. Results: The analysis reveals a dominance of negative sentiment associated with public distrust, institutional dissatisfaction, and concerns over recurring data leaks. Data patterns indicate three systemic drivers of cybersecurity vulnerability: delayed implementation of derivative regulations under the Personal Data Protection Law, technical fragility and centralized risk exposure within the National Data Center, and uneven digital literacy across the population. The findings demonstrate that cybersecurity failures are not isolated technical incidents but reflect broader governance and policy implementation gaps. Conclusions: This study concludes that Indonesia’s digital transformation agenda is constrained by insufficient data-driven cybersecurity governance. The absence of integrated regulatory, technical, and social interventions weakens the state’s capacity to manage digital risks effectively. Limitations: This study is limited to publicly available social media data and does not include direct institutional or field-level validation. Contributions: This research contributes to data science for public policy by demonstrating how social media analytics can support policy diagnosis, risk assessment, and evidence-based cybersecurity reform in digital government systems.